CONCENTRIC MODEL DIVERSIFICATION MODEL OF FARMING FEMALE BUSINESS BASED ON INFORMATION TECHNOLOGY - W., Muslichah Erma; Amartani, Dewi (Advances in Social Sciences Research Journal, 2019)
Land optimization activities were carried out in 5 provinces, namely West Java, Banten, Central Java, DIY and East Java. The existence of a group of women farmers in East Java in the use of land for agriculture, such as fruit and vegetables, should get a response for their follow-up considering the potential activities of women farmer groups. Most of the population in East Java earn a living as farmers and farm labourers. The landowners each cover an area of ​​350m2. The income of women farmers and farm labourers is uncertain depending on the season. It could be when the season is not good they work out of town. So many strategies are poor farmers (farmers with a narrow monthly income of Rp.750,000, and farm labourers earning Rp. 30,000 per day), even though they have to work harder. Research with the title of Information Technology Center Concentric Diversification Model of Information Technology Women. The aim is to minimize disparities in the village. With the use of knowledge and technology, poverty and disparity can be minimized and even eliminated. This study provides macro benefits for stakeholders, namely HR supplying raw materials, farm women who morph into entrepreneurship so that domestic and foreign consumers will get superior products in high-quality regions.